(untitled) (Economics and region, 2020)
The article investigates the essence of socially responsible business and its importance for the strategic development of the tourist enterprises. It is noted that CSR includes business, environmental and social issues, as they have a direct and significant impact on the company, its employees and strategic partners. It is determined that the main principles of CSR are voluntariness, reliability and timeliness, creation of values for all levels of the corporate environment. In the article the classification of strategies for the development of corporate social responsibility (CSR) based on the concept by I. Adizes is determined. The system of evaluation metrics for justification of a CSR directions on the base of the Balanced Scorecard and stakeholder theory is proposed. Strategic profile of CSR for the tourist enterprises is constructed and appropriate strategies for their development are proposed.